2012
DOI: 10.1159/000334900
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and IL-13 in Induced Sputum of COPD and Asthma Patients: Correlation with Respiratory Tests

Abstract: Background: IL-6 is strongly implicated in the development of chronic obstructive pulmonary disease (COPD). IL-13 is the well-documented central mediator in allergic asthma. IL-6 is attributed to the proinflammatory activities in COPD as well as asthma. In COPD patients exacerbation is increased by serum IL-6. The association of IL-13 as well as IL-6 with the impaired respiratory function of asthma patients remains controversial. Objectives: The aim of this study was to compare the concentration of IL-6 and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 72 publications
2
42
1
1
Order By: Relevance
“…Therefore, it was assumed that the IL-6/IL-13 ratio characterizes asthma and COPD more accurately than the levels of either single cytokine, since the level of an individual cytokine may change dynamically in the course of the disease. 19 The results obtained supported this hypothesis. The IL-6/IL-13 ratio in BALF was significantly different in asthma than in COPD, even though there was no difference between BALF sTREM-1 levels in these 2 diseases.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Therefore, it was assumed that the IL-6/IL-13 ratio characterizes asthma and COPD more accurately than the levels of either single cytokine, since the level of an individual cytokine may change dynamically in the course of the disease. 19 The results obtained supported this hypothesis. The IL-6/IL-13 ratio in BALF was significantly different in asthma than in COPD, even though there was no difference between BALF sTREM-1 levels in these 2 diseases.…”
Section: Discussionsupporting
confidence: 60%
“…It has previously been shown that the ratio of IL-6 and IL-13 concentration in induced sputum is significantly different in asthmatics than in COPD patients. 19 To date, the concentration of sTREM-1 in asthma and COPD patients has been evaluated in serum and plasma only. Systemic sTREM-1 levels correlated positively with asthma and COPD severity and negatively with lung function, and are a good marker of neutrophilic inflammation.…”
Section: -14mentioning
confidence: 99%
“…24 The increased serum IL-6 level has been improved in patients with COPD 25 and IL-6 level in the induced sputum of COPD patients is significantly promoted as well compared with that of asthma patients. 26 TNF-a, one of early regulators in immune response, is responsible for stimulating the release of secondary pro-inflammatory cytokines. 27 IL-10 is an anti-inflammatory cytokine.…”
Section: Liu Et Al Hydrogen-rich Saline Inhibits Ts-induced Copd 1537mentioning
confidence: 99%
“…The association of IL-6 and IL-6 receptor a (IL6Ra, CD126) with asthma was reported, suggesting a potential involvement of these molecules in the development of asthma (8)(9)(10)(11)(12). IL-6 can affect T-cell functions including cytokine production, cell proliferation, and survival (8,(13)(14)(15)(16).…”
Section: Memory Cd8mentioning
confidence: 99%